Pengaruh Kesadaran, Kualitas Pelayanan, Pengetahuan Perpajakan, Dan Sanksi Perpajakan Pada Kepatuhan Wajib Pajak Reklame - Permatasari, Mirah; Lely Aryani M, Ni Ketut (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
Public awareness to comply with taxation obligations  play an important role in tax revenue revenue. This study is intended to determine whether taxpayer awareness, service quality, tax knowledge, and perceptions of tax sanctions have an effect on advertisement taxpayer compliance in the Regional Revenue Board of Badung Regency.. The method of determining the sample in this study using incidental sampling techniques with the number of respondents as many as 54 taxpayers. The data analysis technique used is multiple linear regression analysis. The effect of taxpayer awareness, service quality, tax knowledge and perceptions about tax sanctions on advertisement tax compulsory compliance of 98.3%. The effect of taxpayer awareness on advertisement taxpayer compliance is 1%. The effect of service quality on advertisement taxpayer compliance is 2.2%. Knowledge of taxation on advertisement taxpayer compliance is 4.8%. The influence of taxpayer perceptions about tax sanctions on advertisement taxpayer compliance is 92% . Keywords: Taxpayer Compliance, Taxpayer Awareness, Service Quality, Tax Knowledge, Taxpayer Perception About Tax Sanctions.